Development of a Simple, Low-Cost Electric Propulsion System for Electrifying Long-tail Canal Boats: A Case Study in Bangmod Canel, Bangkok - Thunantha, Suphanat; Kumnard, Akarawit; Poolsombat, Sirapob; Sukjai, Yanin; Laoonual, Yossapong (Journal of Research and Applications in Mechanical Engineering, 2024)
This study aims to convert a long-tail boat's propulsion system from an internal combustion engine to an electric motor for enhanced sustainability and reduced environmental impact. The 5-meter boat underwent design modifications, incorporating an electric hub motor connected to the propeller via a power transmission system. Tests conducted in Bangmod Canal, Bangkok, compared the electric and engine-powered boats in terms of energy consumption and noise levels. Results indicated that the electric boat, despite a slightly lower speed, exhibited advantages in energy efficiency and noise reduction. Economic analysis projected a return on investment within 2 years and 8 months, with a notable Internal Rate of Return (IRR) of 26.20%. The electric conversion proved economically superior, offering cost savings, improved quality of life for residents, and mitigation of pollution along the canal.